Answered

Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Inverse Function:
f-¹ (- 3)
f(x) = 6x - 12


Sagot :

       f(x) = 6x - 12
          y = 6x - 12
  y + 12 = 6x - 12 + 12
  y + 12 = 6x
      6         6
¹/₆y + 2 = x
          y = ¹/₆x + 2
     f⁻¹(x) = ¹/₆x + 2
    f⁻¹(-3) = ¹/₆(-3) + 2
    f⁻¹(-3) = -¹/₂ + 2
    f⁻¹(-3) = 1¹/₂
(x, f⁻¹(x)) = (-3, 1¹/₂)